The nitrogen fertiliser value and other agronomic benefits of industrial biowastes - Rigby,H; Smith,SR (Nutrient Cycling in Agroecosystems, 2014)
An estimated 7 million t of industrial biowastes are landspread annually in the UK. Quantitative research into their fertiliser replacement value and agronomic benefit is required to increase their use in agriculture, recycle valuable nutrients, and contribute to the reduction of biodegradable waste sent to landfill. A programme of systematically designed field experiments was established to quantify the agronomic value of a range of industrial biowastes, including examples from the vegetable, meat and dairy processing industries and digested biowastes from industrial aerobic and anaerobic digestion plants. Dewatered anaerobically digested biosolids (DMAD) was included as a reference material. Yield and N offtake responses of perennial ryegrass, at five rates of application of each biowaste type were used to calculate the N equivalency relative to mineral N fertiliser. Liquid thermophilic aerobic digestate (LTAD) of food waste was an effective source of available N, with an N equivalency of 59–76 %. Liquid mesophilic anaerobic co-digestates of livestock slurry and food waste (LcoMAD) had N equivalencies between 68 and 85 %. Vegetable processing waste and brewing waste (yeast) had N equivalency values of 45 and 89 %, respectively. Regarding other nutrient elements, the biowastes were generally a source of P, vegetable wastes were significant sources of K, and DMAD and the dewatered anaerobically digested organic fraction of municipal solid waste (DMADMSW) were effective sources of S. Certain waste types were not effective sources of N for crop growth (e.g. potato processing wastes, kieselguhr) and require further investigation at greater rates of application to determine their agronomic benefit.